2023
DOI: 10.3390/jcm12175533
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Hypomineralization of Second Primary Molars for Molar Incisor Hypomineralization and Other Relationships between Both Developmental Defects of Dental Enamel

María Marcianes,
Pablo García-Camba,
Alberto Albaladejo
et al.

Abstract: Molar incisor hypomineralization (MIH) and hypomineralized second primary molars (HSPM) are dental enamel developmental defects with significant prevalence and psychophysical impact, posing a public health concern. We examined the relationship between HSPM and MIH in 426 children aged 7 to 10 years (213 with MIH, 213 without MIH). The frequency of HSPM was higher in children with MIH (37.1% vs. 11.3%, p < 0.001). However, there was no correlation between MIH severity and presence of HSPM (p = 0.296). In pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…We had previously investigated the predictive value of hypomineralization of second primary molars (HSPM) for MIH, with a clinical emphasis on preventive measures when detecting HSPM in young children. Its results confirmed our hypothesis, demonstrating that the presence of hypomineralized second primary molars (HSPM) in the primary dentition predicts the subsequent development of MIH in permanent teeth [23]. The current branch of the research operates on a distinctly different foundation, seeking potential associations between MIH and other anomalies that share a certain genetic basis.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…We had previously investigated the predictive value of hypomineralization of second primary molars (HSPM) for MIH, with a clinical emphasis on preventive measures when detecting HSPM in young children. Its results confirmed our hypothesis, demonstrating that the presence of hypomineralized second primary molars (HSPM) in the primary dentition predicts the subsequent development of MIH in permanent teeth [23]. The current branch of the research operates on a distinctly different foundation, seeking potential associations between MIH and other anomalies that share a certain genetic basis.…”
Section: Discussionsupporting
confidence: 75%
“…The project comprised two branches: the first aimed to explore the potential relationships between MIH and hypomineralized second primary molars (HSPM), focusing on the predictive value of HSPM for the subsequent development of MIH. The findings from this initial study have been previously reported [23]. In the current branch of the investigation, the objective was to explore the possible association of MIH with two dental anomalies, AG and IODM, which are components of DAP.…”
Section: Methodsmentioning
confidence: 82%